Preparation of Polymer-Derived Microporous Carbon as Storage Media for Methane - , Imam Prasetyo, Rochmadi, Rakhmat Yunanto, Teguh Ariyanto, Wiratn ([Yogyakarta] : Chemical Engineering Department, Gadjah Mada Unive, 2010)
In this research, high surface area microporous carbon for methane storage application was prepared by controlled pyrolysis of specially synthesized polymeric resin at relatively low temperature. The polymeric resins were synthesized through polymerization reaction of phenolic compounds (phenol, para-tert-butyl phenol, and resorcinol) with formaldehyde under acidic catalyst. This research was particularly focused on the development of precursor which can be carbonized at relatively low temperature without any additional activation process to produce high surface area microporous carbon for methane storage application. The use of phenolic compounds combination in the polymerization reaction was aimed to modify polymer network structures of the precursor which lead to microporosity alteration of the carbonized precursor. The precursors were carbonized by thermal decomposition at 450- 750&#8304